The relationship between dietary intake of B vitamins and H. pylori seropositivity - Yuexia Lu; Ting Wang; Shuaipeng Yuan; Jiqi Ouyang; Jinsheng Dong; Xin Jiang; Xiao Shao; Huazhao Xu; Runshun Zhang (PLoS ONE, 2025)
Introduction The association of vitamins with Helicobacter pylori (H. pylori) infection is of great interest yet currently remains controversial. Most studies have focused on serum levels of vitamins, whereas we aimed to detect a correlation between dietary intake of B vitamins and H. pylori infection. Methods We accessed the National Health and Nutrition Examination Survey (NHANES) of U.S. citizens and employed the Full Sample 2-Year mobile examination center (MEC) Examination Weight for data analysis For the 1999–2000 NHANES data period, 3,485 U.S. citizens made up our study.This cross-sectional study analyzed the relationship between dietary B vitamins and H. pylori seropositivity through weighted logistic regression. Variables were used to perform subgroup analyses, and the presence of linear correlation was explored using restricted cubic spline (RCS) plot progression. Results Participants with H. pylori infections displayed lower intakes of vitamins B1, B2, niacin, B6, folate, and B12 compared with those without H. pylori infection. The Odds Ratio values (95% Confidence Interval) of the highest quartile of dietary intake were 0.69 (0.48–0.98), 0.63 (0.49–0.81), 0.69 (0.48–0.97), 0.71 (0.52–0.98), 0.67 (0.51–0.88), and 0.93 (0.66–1.29) for Log Vitamin B1, Log Vitamin B2, Log Niacin, Log Vitamin B6, Log Folate, and Log Vitamin B12, respectively, in comparison to the lowest quartile. Age and ethnicity were found to influence the association between B vitamins consumption and H. pylori infection. Conclusion The dietary intake of vitamins B1, B2, niacin, B6, and folate were inversely correlated with the probability of an H. pylori infection. The mechanisms underlying this association may involve gastrointestinal flora, oxidative stress, as well as immune and mitochondrial regulation.